PENYELESAIAN SENGKETA PEMILIHAN KEPALA DESA DI KABUPATEN INDRAGIRI HILIR (Studi Peraturan Daerah Nomor 7 Tahun 2016 Tentang Pemilihan, Pengangkatan Dan Pemberhentian Kepala Desa) - Wandi; Indra Muchlis Adnan (JURNAL HUKUM DAS SOLLEN, 2017)
Disputes over the Village Head election are more interesting to be discussed since the importance of sustaining the lives of villagers is actually getting away from the initial concept of escorting the democratization process in the village. It takes the wise steps of the conflicting parties, releasing the power to think of the best paths as moral responsibility for the benefit of the people, so as not to affect the implementation of village governance in improving public services and public welfare. The Birth of Regional Regulation of Indragiri Hilir Regency Number 7 Year 2016 concerning the Election, Appointment and Dismissal of Village Head Juncto Regent Regulation Indragiri Hilir Number 61 Year 2016 on Guidance of Implementation of Village Head Election has been explained that Normatif Responsibility responsibility of dispute of Village Head election in Indragiri Hilir settled by the Indragiri Hilir Regent through predetermined tools, and the nature of the decision is final and binding. Related to the report of criminal offense as intended in 72 paragraph (2) letter c shall be submitted to the competent authority in accordance with the prevailing laws and the process of settling the criminal offense shall not affect the election stage.